2013
DOI: 10.1111/bju.12349
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation (RFA) of renal cell carcinoma (RCC): experience in 200 tumours

Abstract: ObjectivesTo evaluate our clinical experience with percutaneous image-guided radiofrequency ablation (RFA) of 200 renal tumours in a large tertiary referral university institution.Patients and MethodsImage-guided RFA (ultrasonography or computed tomography [CT]) of 200 renal tumours in 165 patients from June 2004 to 2012 was prospectively evaluated. Institutional Review Board approval was granted.The treatment response and technical success were defined by absence of contrast enhancement within the tumour on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
132
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 58 publications
(94 reference statements)
6
132
2
11
Order By: Relevance
“…According to our review, extra-renal metastases after imageguided RFA of renal tumors are very rare but slightly more frequent than de novo renal tumors, and occur up to 4.5 years after initial RFA [3]. In a controlled study, the metastasis-free survival after treatment of T1a renal tumors was significantly better for surgery when compared with RFA (p = 0.005).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…According to our review, extra-renal metastases after imageguided RFA of renal tumors are very rare but slightly more frequent than de novo renal tumors, and occur up to 4.5 years after initial RFA [3]. In a controlled study, the metastasis-free survival after treatment of T1a renal tumors was significantly better for surgery when compared with RFA (p = 0.005).…”
Section: Discussionmentioning
confidence: 86%
“…2 defined as no residual unablated tumor and no local tumor progression in the follow-up imaging. 3 for 11 tumors the number of sessions was not indicated. für 11 Tumoren wurde die Anzahl der Behandlungssitzungen nicht angegeben.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The efficacies of ablative therapies, including radiofrequency (RF) ablation (RFA) and cryoablation, have been reported previously: A number of authors have reported long-term results following RFA for RCC and demonstrated excellent oncological outcomes (14)(15)(16)(17)(18)(19)(20). In our institute, percutaneous RFA for renal cancer was initiated in 2005.…”
Section: Introductionmentioning
confidence: 83%